ENGLISH LANGUAGE LEARNING STRATEGIES OF TWO SUCCESSFUL LEARNERS OF DIFFERENT LEARNING STYLES - Kartika Nuswantara (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
This article attempts to present a profile of two successful English language learners who are found to hold strong learning styles. Learning styles are considered as the factors that not only have great influence but are also embedded to the attempt for selecting the strategies used to attack the perplexing learning problems or tasks. The learning strategies as the factor leads a successful learning should be channeled into other factors that juxtapose with this factor. The present article would present how certain affective and cognitive domains of learning styles have made particular learning strategies become effective. By means of a multi case study, that describes two different phenomena and compares them for reducing the risk of error, the present study tries to give more contribution towards the study on the Good Language Learner that has been so far being the concern of many scholars. Such an investigation would help other learners of the same traits or endowment to adopt as well as adapt the strategy. Besides, this can be used as a model for strategy training that is hosted to help less fortunate learners who study English.